2016
DOI: 10.1142/s1088424616500929
|View full text |Cite
|
Sign up to set email alerts
|

Study of the coordination of quinuclidine to a chiral zinc phthalocyanine dimer

Abstract: We attempted the calculation of an accurate equilibrium constant for the dimerization process of enantiomerically pure Zn-1 using UV-vis dilution experiments. At millimolar concentration Zn-1 is involved in a chemical exchange process between its monomeric and dimeric state that is slow on the 1H NMR timescale. We performed variable-temperature 1H NMR experiments in CDCl3 solution to determine the dimerization constant value at different temperatures and performed a van’t Hoff plot to derive the thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…example, the zinc complex of 1 could form a cofacial dimer by stepwise coordination of two quinuclidine molecules (Giménez-Agulló et al, 2016), which was confirmed by the change of absorption spectra and 1 H-NMR signal. In addition, 1 was used to construct chiral bis(phthalocyaninato)yttrium doubledecker complexes 8 and 9 (Zhou et al, 2014), as well as a porphyrin-Pc heteroleptic rare-earth triple decker complex 10 (Wang et al, 2014).…”
Section: Binap and Binap-related Substituent-linked Systems Synthesismentioning
confidence: 72%
“…example, the zinc complex of 1 could form a cofacial dimer by stepwise coordination of two quinuclidine molecules (Giménez-Agulló et al, 2016), which was confirmed by the change of absorption spectra and 1 H-NMR signal. In addition, 1 was used to construct chiral bis(phthalocyaninato)yttrium doubledecker complexes 8 and 9 (Zhou et al, 2014), as well as a porphyrin-Pc heteroleptic rare-earth triple decker complex 10 (Wang et al, 2014).…”
Section: Binap and Binap-related Substituent-linked Systems Synthesismentioning
confidence: 72%